Exploring The Experience Of Using Simulation-Games In Project Management Teaching: A Phenomenographic Approach - Santos, Jorge Alberto dos; Lameras, Petros (Archives of Business Research, 2018)
This research describes how lecturers conceptualize the experience of using simulation-games in the teaching of management, especially project management. The research uses a phenomenographic approach, seeking to explore and categorize teachers’ perception variation. The research was carried out with twelve lecturers from three different universities in the United Kingdom. The data was collected using interviews. The data showed that the variation in teachers’ description of their relationship with simulation-games in teaching management could be synthesized in a set of four different categories, ranging from simulation-games as “resource to improve the acquisition of content” to simulation-games as “a means to bear resemblance to reality”. The main conclusion is that there are two orientations in teachers’ approach to simulation-games: on the one hand, there are those who are interested in delivering some kind of learning goals through it. I called this teachers’ orientation instrumental. On the other hand, there are those for whom simulation-games promote a special kind of bond in students’ relationship which, in turn, help them achieve their learning goals. I called this teachers’ orientation engagement.